High‐throughput screening identifies suppressors of mitochondrial fragmentation in OPA1 fibroblasts. Issue 6 (20th May 2021) - Cretin, Emma; Lopes, Priscilla; Vimont, Elodie; Tatsuta, Takashi; Langer, Thomas; Gazi, Anastasia; Sachse, Martin; Yu‐Wai‐Man, Patrick; Reynier, Pascal; Wai, Timothy
Abstract: Mutations in OPA1 cause autosomal dominant optic atrophy (DOA) as well as DOA+, a phenotype characterized by more severe neurological deficits. OPA1 deficiency causes mitochondrial fragmentation and also disrupts cristae, respiration, mitochondrial DNA (mtDNA) maintenance, and cell viability. It has not yet been established whether phenotypic severity can be modulated by genetic modifiers of OPA1. We screened the entire known mitochondrial proteome (1, 531 genes) to identify genes that control mitochondrial morphology using a first‐in‐kind imaging pipeline. We identified 145 known and novel candidate genes whose depletion promoted elongation or fragmentation of the mitochondrial network in control fibroblasts and 91 in DOA+ patient fibroblasts that prevented mitochondrial fragmentation, including phosphatidyl glycerophosphate synthase ( PGS1 ). PGS1 depletion reduces CL content in mitochondria and rebalances mitochondrial dynamics in OPA1‐deficient fibroblasts by inhibiting mitochondrial fission, which improves defective respiration, but does not rescue mtDNA depletion, cristae dysmorphology, or apoptotic sensitivity. Our data reveal that the multifaceted roles of OPA1 in mitochondria can be functionally uncoupled by modulating mitochondrial lipid metabolism, providing novel insights into the cellular relevance of mitochondrial fragmentation. Synopsis: Phenotypic screening of OPA1 patient fibroblasts identifies multiple genetic suppressors of mitochondrial fragmentation including PGS1, a key enzyme in cardiolipin biosynthesis. PGS1 depletion reduces mitochondrial fission and restores normal mitochondrial morphology to OPA1‐deficient fibroblasts. Mitochondrial morphology defects in human fibroblasts can be automatically imaged and quantified by supervised machine learning, allowing for imaging‐based screening. High‐throughput screening identifies new genes required or the maintenance of mitochondrial morphology in fibroblasts from healthy individuals. High‐throughput screening of OPA1 patient fibroblasts identifies genetic modifiers of mitochondrial fragmentation not previously linked to Dominant Optic Atrophy. Loss of PGS1 in OPA1‐deficient fibroblasts restores mitochondrial morphology and respiration, but not cristae dysmorphology, apoptotic sensitivity, nor mtDNA content. Mitochondrial morphology defects can be functionally uncoupled from other pleiotropic effects of OPA1 loss. Abstract : Phenotypic screening of OPA1 patient fibroblasts identifies multiple genetic suppressors of mitochondrial fragmentation including PGS1, a key enzyme in cardiolipin biosynthesis. PGS1 depletion reduces mitochondrial fission and restores normal mitochondrial morphology to OPA1‐deficient fibroblasts.